2018
DOI: 10.21873/anticanres.12867
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Stratification and Long-term Follow-up of Patients with Periampullary Carcinomas

Abstract: Patients suffering from PDAC have the worst prognosis and greatest benefit from radical resection of all patients with periampullary tumors. More detailed studies are warranted to better distinguish between the different entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…Our data reinforces the reported favorable prognosis seen in patients with DC as opposed to those with PDAC [ 1 ], likely due to differences in tumor biology [ 19 ] and behavior [ 20 ]. Furthermore, we found that R1 resection affected survival among patients with PDAC but did not reach statistical significance in those with DC.…”
Section: Discussionsupporting
confidence: 89%
“…Our data reinforces the reported favorable prognosis seen in patients with DC as opposed to those with PDAC [ 1 ], likely due to differences in tumor biology [ 19 ] and behavior [ 20 ]. Furthermore, we found that R1 resection affected survival among patients with PDAC but did not reach statistical significance in those with DC.…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, the incidence of periampullary tumors has been increasing. According to different histological subtypes, ampullary carcinoma can be divided into intestinal, pancreaticobiliary, and mixed types 1 . If the tumor is larger than 3 cm, with poor differentiation and peripheral nerve invasion, the 5‐year survival rate is only about 24%–42% 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…According to different histological subtypes, ampullary carcinoma can be divided into intestinal, pancreaticobiliary, and mixed types. 1 If the tumor is larger than 3 cm, with poor differentiation and peripheral nerve invasion, the 5-year survival rate is only about 24%-42%. 2,3 Since the particularity of periampullary anatomical structure and the different subtypes of lesions have different treatments and prognoses, 4 an accurate location and qualitative diagnosis identification are essential for periampullary lesions in the early stage.…”
Section: Introductionmentioning
confidence: 99%